A dual colorimetric and near-infrared fluorescent turn-on probe for Hg2+ detection and its applications. (April 2019) - Huang, Liyan; Yang, Zitun; Zhou, Zile; Li, Yaqian; Tang, Siping; Xiao, Wenpei; Hu, Meng; Peng, Cheng; Chen, Yanxia; Gu, Biao; Li, Haitao
Abstract: The increasing Hg 2+ contamination in environment and ecosystem has gained wide attention and thus demands for its facile and effective detection. In this study, we constructed a new fluorescent probe ( E )-2-(2-(3-(1, 3-dithian-2-yl)-4-hydroxystyryl)- 4 H -chromen-4-ylidene)malononitrile (DCM -Hg ) for Hg 2+ detection by incorporating the 1, 3-dithiane group to the dicyanomethylene-4 H -pyran fluorophore for the first time. This probe can selectively detect Hg 2+ via the Hg 2+ -triggered deprotection reaction of thioacetals, which leads to a distinct color change from purple to pink and obvious fluorescence enhancement in the near-infrared (NIR) region. The NIR fluorescence intensity increased linearly with Hg 2+ level within the range from 0 to 100 μM and the detection limit ofDCM -Hg for Hg 2+ was found to be 6.8 × 10 −8  mol/L. Moreover, the probe could sense Hg 2+ on paper strips and image Hg 2+ in living cells with low cytotoxicity, which demonstrates its potential application in environment and biological science. Graphical abstract: Highlights: A novel colorimetric and near-infrared fluorescent probe was developed for Hg 2+ detection. The color and fluorescence changes induced by Hg 2+ showed sharp contrast. DCM-Hg showed excellent sensitivity and high anti-interference ability for Hg 2+ detection. DCM-Hg was successfully applied to detect Hg 2+ on test strips and image Hg 2+ in living cells.